Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Mid-Atlantic)--Atlantic silverside - Fay, Clemon W.; Neves, Richard J.; Pardue, Garland B. (Washington, D.C. U.S. Department of the Interior, 1983)
FWS/OBS-82/11.10
Keywords: Invertebrates; Fishes; History; Atlantic silverside--Mid-Atlantic.